2020
DOI: 10.1002/wer.1403
|View full text |Cite
|
Sign up to set email alerts
|

Urban stormwater characterization, control, and treatment

Abstract: This review summarizes over 280 studies published in 2019 related to the characterization, control, and management of urban stormwater runoff. A summary of quantity and quality concerns is provided in the first section of the review, serving as the foundation for the following sections which focus on the control and treatment of stormwater runoff. Finally, the impact of stormwater control devices at the watershed scale is discussed. Each section provides a self-contained overview of the 2019 literature, common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 285 publications
(331 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that maintenance is of significance for ensuring GI functions effectively [11][12][13][14][15]. In early 2008, it was reported that to keep wet ponds functioning, routine monitoring and regular sediment cleaning are necessary [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that maintenance is of significance for ensuring GI functions effectively [11][12][13][14][15]. In early 2008, it was reported that to keep wet ponds functioning, routine monitoring and regular sediment cleaning are necessary [16].…”
Section: Introductionmentioning
confidence: 99%
“…Stormwater Best Management Practices (BMPs) are an efficient way to implement in urban area due to less permeable area [8]. Stormwater BMPs like wetlands, bioretention, retention ponds and detention ponds have been applied in many developed countries such as United States (US), United Kingdom (UK), China, Japan and German to treat urban runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Stormwater BMPs like wetlands, bioretention, retention ponds and detention ponds have been applied in many developed countries such as United States (US), United Kingdom (UK), China, Japan and German to treat urban runoff. According to a study conducted by Rodak et al [8], the results achieved from stormwater BMPs show excellent performance in removing pollutants from urban runoff.…”
Section: Introductionmentioning
confidence: 99%